The role of autophagy in maintaining intestinal mucosal barrier. Issue 11 (24th April 2019) - Wu, Yanping; Tang, Li; Wang, Baikui; Sun, Qiming; Zhao, Pengwei; Li, Weifen
Abstract: The intestinal mucosal barrier is the first line to defense against luminal content penetration and performs numerous biological functions. The intestinal epithelium contains a huge surface that is lined by a monolayer of intestinal epithelial cells (IECs). IECs are dominant mediators in maintaining intestinal homeostasis that drive diverse functions including nutrient absorption, physical segregation, secretion of antibacterial peptides, and modulation of immune responses. Autophagy is a cellular self‐protection mechanism in response to various stresses, and accumulating studies have revealed its importance in participating physiological processes of IECs. The regulatory effects of autophagy depend on the specific IEC types. This review aims to elucidate the myriad roles of autophagy in regulating the functions of different IECs (stem cells, enterocytes, goblet cells, and Paneth cells), and present the progress of autophagy‐targeting therapy in intestinal diseases. Understanding the involved mechanisms can provide new preventive and therapeutic strategies for gastrointestinal dysfunction and diseases. Abstract : Autophagy plays a pivotal role in the development, differentiation, and functions of intestinal epithelial cells. Thus it is crucial for the maintenance of the intestinal mucosal barrier and homeostasis.